2015
DOI: 10.14434/pders.v34i1.13258
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating Students with Epilepsy or Seizure Disorders: Effective Strategies for Teachers

Abstract: Abstract:The most common chronic neurological condition in children is epilepsy. Because it often occurs in childhood, epilepsy is likely the most common neurological condition encountered by school professionals including teachers. Given the impact that epilepsy can have on academic functioning and specifically on the day-to-day performance of a student in the classroom, it is important for teachers to be aware not only of the presence of the disorder but also of the potential consequences and appropriate way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…In order to reduce school absenteeism and mitigate its effects, children with epilepsy should receive integrated care from a multidisciplinary team covering physicians, teachers, parents, educational psychologists, and social services as appropriate. [57, 58] Their management should extend beyond healthcare to a programme of school-based interventions such as prevention of triggers, a seizure plan, social and emotional support, adaptation of teaching methods, resources and exams, and inclusion of classmates in cooperative learning. [58]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce school absenteeism and mitigate its effects, children with epilepsy should receive integrated care from a multidisciplinary team covering physicians, teachers, parents, educational psychologists, and social services as appropriate. [57, 58] Their management should extend beyond healthcare to a programme of school-based interventions such as prevention of triggers, a seizure plan, social and emotional support, adaptation of teaching methods, resources and exams, and inclusion of classmates in cooperative learning. [58]…”
Section: Discussionmentioning
confidence: 99%
“…[57, 58] Their management should extend beyond healthcare to a programme of school-based interventions such as prevention of triggers, a seizure plan, social and emotional support, adaptation of teaching methods, resources and exams, and inclusion of classmates in cooperative learning. [58]…”
Section: Discussionmentioning
confidence: 99%
“…With the approval of the student’s parents and the student’s consent, peers should be provided with factual, age-appropriate information to relieve their worries and encourage understanding and empathy. 51 …”
Section: Summary Of Evidencementioning
confidence: 99%
“…With the approval of the student's parents and the student's consent, peers should be provided with factual, age-appropriate information to relieve their worries and encourage understanding and empathy. 51 All studies have shown a positive impact of health education on raising knowledge, improving attitude, and enhancing the management of seizure first aid. Attitude toward epileptic patients' education, employment, and marriage also improved significantly after the intervention.…”
mentioning
confidence: 99%
“…A par da família, os professores podem ser ativos e valiosos na monitorização de efeitos colaterais, potenciais, de terapêutica ou da atividade convulsiva de um estudante. Estes podem identificar mudanças percetíveis no comportamento do aluno, nas emoções, na capacidade intelectual ou na atividade convulsiva (13,14) .…”
unclassified